Pemberdayaan kelompok masyarakat Kecamatan Tampan Kota Pekanbaru dalam program inovasi teknologi pengering berbasis biomassa yang ramah lingkungan untuk meningkatan kualitas dan kuantitas produk makanan berbahan baku ubi - Juandi Muhammad; Herman Herman; Gimin Gimin; Joko Risanto; Syahril Syahril (Unri Conference Series: Community Engagement, 2020)
The potential of the agricultural sector in terms of cassava in Tampan District, Pekanbaru City with a total potential of 11,210 tonnes of cassava (based on BPS data, 2019). This enormous potential has led to the growth of SMEs for community groups to take advantage of these opportunities in the business of producing cassava-based food processing. Furthermore, this potential is an opportunity for local governments to create a market or regional superior product as well as an attraction for citizens from outside the region to come to Tampan District because it can form an agro-industry in the field of cassava chips. The attraction for visitors to stop by at Tampan District is also supported by geographical aspects, transportation that is easily accessible to everyone. Through this community service activity, the fostered village scheme is very appropriate to be applied in Tampan District because it can guide UKM groups so that at the end of the service activities of this guided village scheme will form superior regional products that are competitive through the application of environmentally friendly biomass energy-based drying technology, and the application of IT-based management system so that at the end of the activity it will produce an Agro-Industry target village with regional superior products that are competitive.